Polyurethane structural adhesive and preparation method thereof

By introducing polyamides similar to nylon to polyurethane structural glue and combining modified castor oil and silane coupling agent, the problem of low wettability of polyurethane adhesives to nylon materials is solved, high strength and stable adhesive properties are achieved, and suitable for applications such as electronic components.

CN119614137APending Publication Date: 2025-03-14SUZHOU TIANMAI THERMAL TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411699819.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

When bonding to nylon materials, the two-component polyurethane adhesive has a regular molecular structure and high crystallinity, resulting in low wettability, which in turn shows poor adhesiveness.

Method used

By introducing low-molecular-weight liquid polyamides with similar molecular structure to those of nylon materials, and combining modified castor oil and silane coupling agents, wetting and interface interactions between the polyurethane structural glue and the nylon substrate are enhanced.

Benefits of technology

It improves the bonding strength and stability of polyurethane structural glue to nylon substrates, enhances its moisture and heat resistance in high temperature and high humidity environments, and meets the high-strength bonding needs of nylon substrates such as electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119614137A_ABST
    Figure CN119614137A_ABST
Patent Text Reader

Abstract

The invention discloses a polyurethane structural adhesive and a preparation method thereof. The polyurethane structural adhesive comprises a first component and a second component, the first component is prepared from the following components in parts by weight: 20 to 45 parts of castor oil, 10 to 30 parts of modified castor oil, 5 to 15 parts of polyether polyol, 1 to 10 parts of chain extender, 0.5 to 8 parts of polyamide, 10 to 35 parts of first filler, 0.1 to 1 part of silane coupling agent and 0.0 to 0.1 part of catalyst; the second component is prepared from the following components in parts by weight: 3 to 15 parts of polyisocyanate, 75 to 95 parts of polyurethane prepolymer, 2 to 5 parts of second filler and 0.1 to 0.5 part of water removal agent; wherein the polyurethane prepolymer is a polyisocyanate prepolymer obtained through a reaction of polyether polyol and polyisocyanate. The polyurethane structural adhesive provided by the invention has good mechanical properties and bonding strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of materials, and in particular to a polyurethane structural adhesive and a preparation method thereof. Background Art

[0002] Two-component polyurethane adhesives are composed of a liquid component A containing hydroxyl groups and a liquid component B containing NCO groups. When used, the components A and B are mixed evenly in a certain ratio. The molecular structure of the cured product contains more polar groups such as urethane bonds and urea bonds, so it has good adhesion to a variety of substrates. Due to the unique soft and hard structure of polyurethane, it has a certain degree of cold resistance and temperature resistance. Therefore, two-component polyurethane adhesives are the most diverse, largest-dosage, and most widely used products among PUs.

[0003] Nylon material, which is widely used in electronic component housings, has a regular molecular structure and high crystallinity, which makes it difficult for adhesives to penetrate it, resulting in poor adhesion. In addition, there are many varieties of nylon materials, and the bondability of different varieties of nylon materials varies. Some nylon materials are also mixed with glass-reinforced fibers, which brings variables to the bonding, making the bonding of some nylon materials difficult. How to solve the problem of low wettability of polyurethane adhesives for materials with high crystallinity such as nylon? There is currently no relevant technical solution disclosed. Only 3M has launched a two-component polyurethane adhesive suitable for nylon bonding. TM Scotch-Weld TM DP6310NS / DP6330 NS series products.

[0004] To this end, the present invention adopts the principle of similar polarity and similar miscibility, and introduces a low molecular weight liquid polyamide with a molecular structure similar to that of nylon material, thereby improving the wettability of the polyurethane adhesive to the nylon material, thereby improving the adhesion.

[0005] Chinese patent number CN117551413A discloses a polyurethane hot melt adhesive for nylon bonding, wherein the polymer components include the following raw materials in parts by weight: 15 to 50 parts of a self-made linear polyester polyol containing an amide group; 10 to 40 parts of a polyester polyol; 20 to 50 parts of a polyether polyol; 0.3 to 0.5 parts of an antioxidant; 15 to 20 parts of an isocyanate; 0.2 to 0.5 parts of a coupling agent; and 0.1 to 0.5 parts of a catalyst. Since the self-made linear polyester polyol containing an amide group is a solid product, it is not suitable for preparing a liquid two-component solvent-free polyurethane adhesive.

[0006] The present invention solves at least one of the above problems. Summary of the invention

[0007] The purpose of the present invention is to provide a polyurethane structural adhesive and a preparation method thereof. The tensile strength of the polyurethane structural adhesive prepared by the present invention reaches more than 10MPa, and the elongation at break reaches more than 90%, indicating that it has good physical and mechanical properties. The shear strength of bonding nylon substrates is stable at more than 5MPa, indicating that it has high bonding strength and has good bonding performance and stability; and its shear strength in a high temperature and high humidity environment is also stable at more than 5MPa, indicating that it also has good moisture and heat resistance, and can be used for bonding nylon substrates such as electronic components to meet its high-strength bonding requirements.

[0008] The purpose of the present invention is achieved by the following technical solutions:

[0009] In a first aspect of the present invention, there is provided a polyurethane structural adhesive comprising a first component and a second component;

[0010] The first component comprises, by weight: 20-45 parts of castor oil, 10-30 parts of modified castor oil, 5-15 parts of polyether polyol, 1-10 parts of chain extender, 0.5-8 parts of polyamide, 10-35 parts of first filler, 0.1-1 parts of silane coupling agent, and 0.0-0.1 parts of catalyst;

[0011] The second component comprises, by weight: 3 to 15 parts of polyisocyanate, 75 to 95 parts of isocyanate prepolymer, 2 to 5 parts of second filler, and 0.1 to 0.5 parts of dewatering agent;

[0012] Wherein, the polyurethane prepolymer is a polyisocyanate prepolymer obtained by reacting polyether polyol and polyisocyanate.

[0013] Compared with the prior art, the invention has the beneficial effects of: by using the mixture of modified castor oil and castor oil, the wettability between the polyurethane structural adhesive and the nylon substrate can be enhanced; by using the silane coupling agent to improve the interface interaction between the polyurethane structural adhesive and the nylon substrate, the bonding strength of the polyurethane structural adhesive to the nylon substrate is improved; and by introducing polyamide similar to the nylon structure, the interfacial tension between the nylon substrate and the polyurethane structural adhesive is reduced by using the principle of similar compatibility and similar polarity, thereby further improving the bonding strength of the polyurethane structural adhesive and increasing the bonding force of the polyurethane structural adhesive to the nylon substrate, so as to be better applied to the structural bonding of the nylon substrate of electronic components.

[0014] In some possible implementations, the modified castor oil is one or more of modified castor oil AC-006 and modified castor oil AC-009.

[0015] In some possible implementations, the polyether polyol is one or more of polyether polyol DL2000D and polyether polyol EP330N.

[0016] In some possible implementations, the silane coupling agent is one or more of silane coupling agent KH-560, silane coupling agent CG-1146, and silane coupling agent KH-550.

[0017] In some possible implementations, the polyamide is one or more of polyamide 650, polyamide 651, and polyamide 300#.

[0018] In some possible implementations, the polyisocyanate is one or more of polyisocyanate MDILL, polyisocyanate MDI-50, and polyisocyanate M20S.

[0019] In some possible implementations, the first filler is one or more of HY-S01, HY-S02, LD-200C, LD-400C, and JLH-03-B; and / or

[0020] The chain extender is one or more of dipropylene glycol, glycerol, and 1,4-butanediol; and / or

[0021] The catalyst is one or more of dibutyltin dilaurate, bismuth neodecanoate and triethylenediamine.

[0022] In some possible embodiments, the water scavenger includes one or more of oxazolidine ALT-201 and oxazolidine PTSI; and / or

[0023] The second filler is one or more of AEROSIL R202, HB-131, and KS-150.

[0024] In some possible implementations, the NCO content of the polyurethane prepolymer is 10-20%.

[0025] In some possible implementations, the weight ratio of the first component to the second component is 0.8-1.

[0026] A second aspect of the present invention provides a method for preparing a polyurethane structural adhesive, comprising:

[0027] Preparation of the first component: castor oil, modified castor oil, polyether polyol and chain extender are added to a reaction kettle in sequence, the temperature of the reaction kettle is raised from room temperature to 110-130° C., vacuum dehydration is performed in the reaction kettle, the mixture is transferred to a dynamic mixer, and the mixture is cooled to room temperature; a silane coupling agent, a catalyst and a first filler are added, and the mixture is discharged after being stirred evenly to obtain the first component;

[0028] Preparation of the second component: stirring the isocyanate, the isocyanate prepolymer, the second filler and the dehydrating agent until uniform, and then discharging the mixture to obtain the second component;

[0029] Preparation of polyurethane structural adhesive: The first component and the second component are mixed evenly to obtain polyurethane structural adhesive. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The present invention is a flowchart of a method for preparing a polyurethane structural adhesive according to an embodiment of the present invention. DETAILED DESCRIPTION

[0031] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided to make the present invention more comprehensive and complete and to fully convey the concepts of example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their repeated description will be omitted.

[0032] This embodiment provides a polyurethane structural adhesive, including a first component and a second component.

[0033] The first component comprises, by weight: 20-45 parts of castor oil, 10-30 parts of modified castor oil, 5-15 parts of polyether polyol, 1-10 parts of chain extender, 0.5-8 parts of polyamide, 10-35 parts of first filler, 0.1-1 parts of silane coupling agent and 0.0-0.1 parts of catalyst.

[0034] The second component comprises, by weight, 3 to 15 parts of polyisocyanate, 75 to 95 parts of polyurethane prepolymer, 2 to 5 parts of second filler, and 0.1 to 0.5 parts of water remover.

[0035] It should be noted that the polyurethane prepolymer in the present application is a polyisocyanate prepolymer obtained by reacting a polyether polyol and a polyisocyanate.

[0036] The present application introduces low-polarity castor oil and modified castor oil into the polyurethane structural adhesive, so that the polyurethane structural adhesive can effectively spread and cover the surface of a substrate with high crystallinity such as nylon when it contacts the substrate, thereby achieving a good wetting effect. The modified castor oil can further enhance the wettability of castor oil on substrates such as nylon, improve the interaction between castor oil and nylon, and make it more suitable for surface wetting of substrates with high crystallinity such as nylon.

[0037] The mixed use of modified castor oil and castor oil can enhance the adhesion and curing speed between polyurethane structural adhesive and nylon substrate.

[0038] The interfacial interaction between the polyurethane structural adhesive and the nylon substrate is improved by using a silane coupling agent, thereby increasing the bonding strength of the polyurethane structural adhesive to the nylon substrate. Then, by introducing polyamide having a similar structure to nylon and utilizing the principle of similar compatibility and similar polarity, the interfacial tension between the nylon substrate and the polyurethane structural adhesive is reduced, thereby further increasing the bonding strength of the polyurethane structural adhesive and increasing the bonding strength of the polyurethane structural adhesive to the nylon substrate, thereby making it better applicable to the structural bonding of nylon substrates of electronic components.

[0039] The polyurethane structural adhesive of the present application has good bonding strength, including tensile strength, elongation at break and shear strength, as well as good stability, including moisture and heat resistance, and can be used for the infiltration bonding of nylon substrates such as electronic components to meet high-strength bonding requirements.

[0040] In a preferred embodiment, the weight ratio of castor oil to modified castor oil is 1:1 to 2:1, for example, 1:1, 1.5:1, or 2:1.

[0041] In some specific embodiments, the modified castor oil in the first component is one or more of modified castor oil AC-006 and modified castor oil AC-009. The polyether polyol is one or more of polyether polyol DL2000D and polyether polyol EP330N. The chain extender is one or more of dipropylene glycol, glycerol, and 1.4 butanediol. The polyamide is one or more of polyamide 650, polyamide 651, and polyamide 300#. The first filler is one or more of nano calcium carbonate HY-S01, nano calcium carbonate HY-S02, heavy calcium carbonate LD-200C, heavy calcium carbonate LD-400C, and molecular sieve JLH-03-B. The catalyst is one or more of dibutyltin dilaurate, bismuth neodecanoate, and triethylenediamine. The silane coupling agent is one or more of silane coupling agent KH-560, silane coupling agent CG-1146, and silane coupling agent KH-550.

[0042] In a preferred embodiment, the silane coupling agent KH-560 is selected.

[0043] Silane coupling agent KH-560 can form a "molecular bridge" between polyurethane structural adhesive and nylon substrate. As a bridge, it tightly connects polyurethane structural adhesive and nylon substrate through chemical bonds, forming a strong chemical bonding interface, which significantly enhances the adhesion between polyurethane structural adhesive and nylon substrate.

[0044] It should be further explained that KH-560 can also improve the wettability and dispersibility of polyurethane structural adhesive, allowing it to better penetrate into the surface of nylon substrate and further enhance interfacial interaction.

[0045] In some specific embodiments, the polyisocyanate in the second component is one or more of polyisocyanate MDILL, polyisocyanate MDI-50, and polyisocyanate M20S. The second filler is one or more of fumed silica AEROSIL R202, HB-131, and KS-150. The dewatering agent includes one or more of oxazolidine ALT-201 and oxazolidine PTSI.

[0046] In some specific embodiments, the NCO (isocyanate group) content of the polyurethane prepolymer is 10-20%. In a preferred embodiment, the NCO content is 13.4%.

[0047] In some specific embodiments, the weight ratio of the first component to the second component is 0.8-1. In a preferred embodiment, the weight ratio of the first component to the second component is 1.

[0048] Combined with Figure 1 As shown, the present application also provides a method for preparing a polyurethane structural adhesive, comprising steps S1 to S3.

[0049] Step S1: preparing the first component: castor oil, modified castor oil, polyether polyol and chain extender are added to a reactor in sequence, the temperature of the reactor is raised from room temperature to 110-130° C., vacuum dehydration is performed in the reactor, the reactor is transferred to a dynamic mixer, and the temperature is lowered to room temperature; a silane coupling agent, a catalyst and a first filler are then added, and the material can be discharged after being stirred evenly to obtain the first component.

[0050] Step S2: preparing the second component: stirring the isocyanate, the isocyanate prepolymer, the second filler and the dehydrating agent until they are uniformly mixed and then discharged to obtain the second component.

[0051] Step S3: preparing polyurethane structural adhesive: uniformly mixing the first component and the second component in a volume ratio of 1:1 to obtain polyurethane structural adhesive.

[0052] The technical solution of the present application will be described in more detail below, but it should be understood that the following examples are only for explaining and illustrating the technical solution, but do not limit the scope of the present application. Moreover, unless otherwise specified, the various raw materials, reaction equipment, detection equipment and methods used in the following examples are all known in the art.

[0053] The raw material grades and manufacturers in the examples of this application are shown in Table 1 below.

[0054] Table 1: Raw material brands and manufacturers

[0055]

[0056]

[0057] Example 1

[0058] A polyurethane structural adhesive is prepared by the following preparation method, comprising steps S1 to S3.

[0059] Step S1: preparing the first component: castor oil, modified castor oil, polyether polyol, polyamide and chain extender are added into the material cylinder of the dynamic mixer in sequence, the temperature of the material cylinder is raised from room temperature to 120°C, the vacuum degree is maintained below -0.085Mpa, dehydrated for 1 hour, cooled to room temperature, and then silane coupling agent, catalyst and first filler are added, and the material can be discharged after being stirred evenly to obtain the first component.

[0060] Among them, castor oil 39 weight parts, AC-009 18 weight parts, DL2000D 7.5 weight parts, polyamide 650 3 weight parts, dipropylene glycol 1 weight part, glycerol 2 weight parts, nano calcium carbonate 23 weight parts, molecular sieve JLH-03-B 6 weight parts, KH560 0.5 weight part, catalyst dibutyltin dilaurate 0.002 weight part.

[0061] Step S2: preparing the second component: stirring the isocyanate, the isocyanate prepolymer, the second filler and the dehydrating agent in a dynamic mixer, and discharging the mixture after stirring evenly to obtain the second component.

[0062] Among them, polyisocyanate MDI LL 8 parts by weight, isocyanate prepolymer PP-1 87.85 parts by weight, meteorological silica KS150 4 parts, dehydrating agent PTSI 0.15. Among them, polyisocyanate prepolymer PP-1 is prepared by mixing liquefied polyisocyanate MDI-50 and dehydrated polyether polyol EP-330N at a feed ratio of 5:5 and reacting at 80°C for 2h, and the NCO content in polyisocyanate prepolymer PP-1 is 13.4%.

[0063] Step S3: preparing a polyurethane structural adhesive: uniformly mixing the first component and the second component in a volume ratio of 1:1 to obtain a polyurethane structural adhesive.

[0064] Example 2

[0065] The difference from Example 1 is:

[0066] The first component: 41 parts by weight of castor oil, 15 parts by weight of AC-009, 6.5 parts by weight of DL2000D, 2 parts by weight of polyamide 650, 2.5 parts by weight of dipropylene glycol, 1.5 parts by weight of glycerol, 27 parts by weight of nano calcium carbonate, 4 parts by weight of molecular sieve JLH-03-B, 0.5 parts by weight of KH560, and 0.002 parts by weight of catalyst dibutyltin dilaurate.

[0067] 8.5 parts by weight of polyisocyanate MDI LL, 86.35 parts by weight of isocyanate prepolymer PP-1, 5 parts of fumed silica KS150, and 0.15 parts of water remover PTSI.

[0068] Example 3

[0069] The difference from Example 1 is:

[0070] The first component: 42 parts by weight of castor oil, 21 parts by weight of AC-009, 11 parts by weight of DL2000D, 6.5 parts by weight of polyamide 650, 0.5 parts by weight of dipropylene glycol, 2.5 parts by weight of glycerol, 13 parts by weight of nano calcium carbonate, 3 parts by weight of molecular sieve JLH-03-B, 0.5 parts by weight of KH560, and 0.002 parts by weight of catalyst bismuth neodecanoate.

[0071] The second component: 11 parts by weight of MDI LL, 85.35 parts by weight of isocyanate prepolymer PP-1, 3.5 parts of fumed silica KS150, and 0.15 parts of water remover PTSI.

[0072] Example 4

[0073] The difference from Example 1 is:

[0074] The first component: 25 parts by weight of castor oil, 27 parts by weight of AC-006, 12.5 parts by weight of DL2000D, 1 part by weight of polyamide 650, 4.5 parts by weight of dipropylene glycol, 1.5 parts by weight of glycerol, 20 parts by weight of nano calcium carbonate, 8 parts by weight of molecular sieve JLH-03-B, 0.5 parts by weight of KH560, and 0.002 parts by weight of catalyst bismuth neodecanoate.

[0075] The second component: 9.5 parts by weight of polyisocyanate MDI LL, 86.35 parts by weight of isocyanate prepolymer PP-1, 4 parts of fumed silica KS150, and 0.15 parts of water remover PTSI.

[0076] Example 5

[0077] The difference from Example 1 is:

[0078] The first component: 40.4 parts by weight of castor oil, 20 parts by weight of AC-009, 7 parts by weight of DL2000D, 1.5 parts by weight of polyamide 650, 0.5 parts by weight of dipropylene glycol, 2.1 parts by weight of glycerol, 23 parts by weight of nano calcium carbonate, 5 parts by weight of molecular sieve JLH-03-B, 0.5 parts by weight of KH560, and 0.002 parts by weight of catalyst dibutyltin dilaurate.

[0079] The second component: 8 parts by weight of polyisocyanate MDI LL, 86.85 parts by weight of isocyanate prepolymer PP-1, 5 parts of fumed silica KS150, and 0.15 parts of water remover PTSI.

[0080] Example 6

[0081] The difference from Example 1 is:

[0082] The first component: 29.7 parts by weight of castor oil, 18 parts by weight of AC-009, 10.5 parts by weight of DL2000D, 2 parts by weight of polyamide 650, 3.5 parts by weight of dipropylene glycol, 1.8 parts by weight of glycerol, 30 parts by weight of nano calcium carbonate, 4 parts by weight of molecular sieve JLH-03-B, 0.5 parts by weight of KH560, and 0.002 parts of dibutyltin dilaurate as catalyst.

[0083] The second component: 12.5 parts by weight of polyisocyanate MDI LL, 83.35 parts by weight of isocyanate prepolymer PP-1, 4 parts of fumed silica KS150, and 0.15 parts of water remover PTSI.

[0084] Comparative Example 1

[0085] The difference from Example 5 is that castor oil and modified castor oil AC-009 are not added.

[0086] Comparative Example 2

[0087] The difference from Example 5 is that polyamide 650 is not added.

[0088] In order to verify the performance of the product of the present application, the following tests were conducted on the polyurethane structural adhesives of the above embodiments and comparative examples. The test results are shown in Table 2.

[0089] (I) Mechanical properties test: The tensile strength and elongation at break of the above polyurethane structural adhesive samples were tested according to the national standard GB-T1040.1-2006.

[0090] (ii) Bond strength test: The above polyurethane structural adhesive was coated on nylon 12 substrates respectively, and then overlapped and pressed. The specific test method can refer to the national standard GB-T7124-1986, which will not be described here.

[0091] Note: The bonding strength of the above polyurethane structural adhesive samples is verified by their shear strength under different environments, as follows:

[0092] First shear strength test: The test was conducted after curing for 7 days at room temperature of 25±2°C / 50%RH, and the first shear strength was tested using a universal testing machine.

[0093] Second shear strength test: Place the sample in a high temperature and humidity environment of 85°C / 85%RH for 1000 hours, then place it at room temperature for 48 hours, and then use a universal testing machine to test its second shear strength.

[0094] Note: The form of bond failure when the polyurethane structural adhesive is coated on a nylon 12 substrate and the bonding strength is tested can be seen by visual inspection.

[0095] Table 2: Test data of polyurethane structural adhesives of embodiments and comparative examples

[0096]

[0097]

[0098] It can be seen from Table 2 that the tensile strength of the polyurethane structural adhesive prepared by the present invention reaches more than 10 MPa, and the elongation at break reaches more than 90%, indicating that it has good physical and mechanical properties, and the shear strength of bonding nylon 12 substrate is stable at more than 5 MPa, indicating that it has high bonding strength and has good bonding performance and stability; and its shear strength in a high temperature and high humidity environment is also stable at more than 5 MPa, indicating that it also has good moisture and heat resistance, and can be used for the bonding of nylon substrates such as electronic components to meet its high-strength bonding requirements.

[0099] It can be seen from Example 5 and Comparative Example 1 that the addition of castor oil and modified castor oil can significantly increase the shear strength of the polyurethane structural adhesive at room temperature and in a heat-resistant environment, and improve the bonding performance of the polyurethane structural adhesive.

[0100] It can be seen from Example 5 and Comparative Example 2 that the addition of polyamide can significantly increase the shear strength of the polyurethane structural adhesive at room temperature and in a heat-and-humidity environment, and improve the bonding performance of the polyurethane structural adhesive.

[0101] The two-component polyurethane structural adhesive prepared by Examples 1 to 6 exhibits relatively excellent bonding performance and moisture-heat aging resistance relative to Comparative Examples 1-2, and visually inspects the bonding failure forms of Example 3 in the first shear test and the second shear test, and Example 6 in the second shear test as substrate damage, indicating that Example 3 is the optimal example with the best bonding performance.

[0102] By introducing low-polarity castor oil and modified castor oil, the structural adhesive (adhesive) of the present application can well wet the nylon substrate, and secondly, by partially introducing polyamide with a similar structure to nylon, the adhesive force of the adhesive to the substrate is further improved by utilizing the principle of similar compatibility and similar polarity. The two-component polyurethane structural adhesive prepared by the present invention has the advantages of high bonding strength, good physical and mechanical properties and moisture and heat resistance, and has achieved good technical effects, and can be applied to the bonding of nylon materials of electronic components.

[0103] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. A person skilled in the art may change, modify, substitute and modify the above embodiments within the scope of the invention without departing from the principles and purpose of the present invention. All such changes should fall within the scope of protection of the claims of the present invention.

Claims

1. A polyurethane structural adhesive, characterized in that: comprising a first component and a second component; The first component comprises, by weight: 20-45 parts of castor oil, 10-30 parts of modified castor oil, 5-15 parts of polyether polyol, 1-10 parts of chain extender, 0.5-8 parts of polyamide, 10-35 parts of first filler, 0.1-1 parts of silane coupling agent, and 0.0-0.1 parts of catalyst; The second component comprises, by weight: 3 to 15 parts of polyisocyanate, 75 to 95 parts of polyurethane prepolymer, 2 to 5 parts of second filler, and 0.1 to 0.5 parts of dewatering agent; Wherein, the polyurethane prepolymer is a polyisocyanate prepolymer obtained by reacting polyether polyol and polyisocyanate.

2. The polyurethane structural adhesive according to claim 1, characterized in that: The modified castor oil is one or more of modified castor oil AC-006 and modified castor oil AC-009.

3. The polyurethane structural adhesive according to claim 1, characterized in that: The polyether polyol is one or more of polyether polyol DL2000D and polyether polyol EP330N.

4. The polyurethane structural adhesive according to claim 1, characterized in that: The silane coupling agent is one or more of silane coupling agent KH-560, silane coupling agent CG-1146, and silane coupling agent KH-550.

5. The polyurethane structural adhesive according to claim 1, characterized in that: The polyamide is one or more of polyamide 650, polyamide 651, and polyamide 300#.

6. The polyurethane structural adhesive according to claim 1, characterized in that: The polyisocyanate is one or more of polyisocyanate MDILL, polyisocyanate MDI-50, and polyisocyanate M20S.

7. The polyurethane structural adhesive according to claim 1, characterized in that: The first filler is one or more of nano calcium carbonate HY-S01, nano calcium carbonate HY-S02, heavy calcium carbonate LD-200C, heavy calcium carbonate LD-400C, and molecular sieve JLH-03-B; and / or The chain extender is one or more of dipropylene glycol, glycerol, and 1,4-butanediol; and / or The catalyst is one or more of dibutyltin dilaurate, bismuth neodecanoate and triethylenediamine.

8. The polyurethane structural adhesive according to claim 1, characterized in that: The dehydrating agent includes one or more of oxazolidine ALT-201 and oxazolidine PTSI; and / or The second filler is one or more of fumed silica AEROSIL R202, HB-131, and KS-150.

9. The polyurethane structural adhesive according to claim 1, characterized in that: The weight ratio of the first component to the second component is 0.8-1.

10. A method for preparing a polyurethane structural adhesive, characterized in that: include: Preparation of the first component: castor oil, modified castor oil, polyether polyol and chain extender are added to a reaction kettle in sequence, the temperature of the reaction kettle is raised from room temperature to 110-130° C., vacuum dehydration is performed in the reaction kettle, the mixture is transferred to a dynamic mixer, and the mixture is cooled to room temperature; a silane coupling agent, a catalyst and a first filler are added, and the mixture is discharged after being stirred evenly to obtain the first component; Preparation of the second component: stirring the isocyanate, the isocyanate prepolymer, the second filler and the dehydrating agent until uniform, and then discharging the mixture to obtain the second component; Preparation of polyurethane structural adhesive: The first component and the second component are mixed evenly to obtain polyurethane structural adhesive.

Citation Information

Patent Citations

  • Polyurethane hot melt adhesive for nylon bonding and preparation method thereof

    CN117551413A